Wyniki badań naukowych a scenariusz filmowy, czyli od danych empirycznych do fabuły filmu - Peret-Drążewska, Paulina (Kultura-Społeczeństwo-Edukacja, 2016)
This article is an attempt to show the relationship between the findings and the scenario film in the results of research conducted by Jacek Kurzępa and the film Piggies directed by Robert Gliński. This is an exemplification contribution to the debate on the role of film in education and educational function of the film, which can be an attractive and effective means of communication.